2013
DOI: 10.1016/j.acra.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Macromolecular Cascade-Polymer Contrast Medium for Dynamic Contrast-Enhanced MRI Monitoring of Antiangiogenic Bevacizumab Therapy in a Human Melanoma Model

Abstract: Rationale and Objectives To assess the applicability of a novel macromolecular polyethylene glycol (PEG)-core gadolinium contrast agent for monitoring early antiangiogenic effects of bevacizumab using dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI). Materials and Methods Athymic rats (n = 26) implanted with subcutaneous human melanoma xenografts underwent DCE-MRI at 2.0 T using two different macromolecular contrast agents. The PEG core cascade polymer PEG12,000-Gen4-(Gd-DOTA)16, designed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In one human study, K trans and v p were reported to be significantly decreased in glioblastoma patients 24 h after the administration of bevacizumab ( Port et al , 2010 ), consistent with our results in OS. In preclinical animal studies, permeability in DCE-MRI was reported to significantly decline 24 h after a single dose of bevacizumab in a human melanoma model ( Cyran et al , 2013 ), but results in other studies 3 days after bevacizumab treatment in a breast xenograft model were inconsistent with increased v p ( Moestue et al , 2013 ) but decreased K trans ( Kim et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one human study, K trans and v p were reported to be significantly decreased in glioblastoma patients 24 h after the administration of bevacizumab ( Port et al , 2010 ), consistent with our results in OS. In preclinical animal studies, permeability in DCE-MRI was reported to significantly decline 24 h after a single dose of bevacizumab in a human melanoma model ( Cyran et al , 2013 ), but results in other studies 3 days after bevacizumab treatment in a breast xenograft model were inconsistent with increased v p ( Moestue et al , 2013 ) but decreased K trans ( Kim et al , 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in oncology, perfusion mapping (as a surrogate measure of blood flow) correlates with response to tyrosine-kinase inhibitor therapy in patients with renal tumors [ 200 ], and quantitative kinetic parameters of lesion enhancement at DCE can predict whether triple-negative breast cancer patients will respond to neoadjuvant chemotherapy [ 201 ]. Animal studies have suggested that quantitative tumor vascularity and perfusion parameters can act as surrogate descriptors for the effect of sorafenib therapy on prostate carcinoma within a week [ 172 ] and that, in conjunction with novel contrast agents, the DCE MRI profile is able to indicate early (within 24 h) endothelial permeability changes following bevacizumab therapy in a melanoma model [ 202 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…32 At the same, in contrast with small molecular MR contrast medium (eg, Gd-DTPA), these dendrimer-based nanoparticles are a type of intracellular medium that makes it feasible to track therapeutic agents at the cellular level. 33 In our study, these nanoparticles produced a relatively high signal intensity that washed out slowly when compared with Gd-DTPA (Figure 4).…”
Section: Resultsmentioning
confidence: 92%